Buddhist Meditation for Christian Contemplatives: Useful and Tricky - Feldmeier, Peter (Buddhist Christian studies, 2021)
This paper argues that all spiritual paths and attainments are locatable only in their own traditions that have their own logic, culture, and interpretive lenses. Within this first principle, one can see that there are possibilities for a skillful use of Buddhist practices in a Christian contemplative agenda. The author argues that Buddhist practices could serve various purposes: as a contemplative augment; as a direct facilitating of a Christian contemplative agenda; and as a way of providing what might be missing in traditional contemplative practices. They ought to be approached, however, to the degree that they can assist a robust Christian spirituality. Limitations can be theoretical, theological, or practical, and these need to be respected. Given respect for the Christian agenda and limitations inherent in the differences between the two traditions, the author commends the practice of vipassana or insight meditation as a way of facilitating what John of the Cross calls active nights of the senses and spirit. Furthermore, Buddhist samadhi practices of the divine-abiding meditations could augment what might be missing in an all too constricted Christian contemplative spiritual posture. The author also argues that these Buddhists practices can only go so far in assisting a Christian contemplative agenda and that their authentic usages as well as the original agenda of these usages should be respected as religiously different.